Methods of prevention of calcium deficiency in pediatric practice - TE Taranushenko; NG Kiseleva; TV Ovchinnikova (Archives of Preventive Medicine - Peertechz Publications, 2022)
It is known that the prevention of deficiency conditions in children is one of the most urgent tasks of preventive pediatrics. The importance of timely recommendations for optimizing the replenishment of microelements and vitamins is undeniable, and understanding the importance of using calcium and vitamin D supplements significantly reduces the risk of adverse health effects in childhood and later life.